Bright Lu2O3:Eu Thin‐Film Scintillators for High‐Resolution Radioluminescence Microscopy. Issue 14 (16th July 2015) - Sengupta, Debanti; Miller, Stuart; Marton, Zsolt; Chin, Frederick; Nagarkar, Vivek; Pratx, Guillem
Abstract : The performance of a new thin‐film Lu2 O3 :Eu scintillator for single‐cell radionuclide imaging is investigated. Imaging the metabolic properties of heterogeneous cell populations in real time is an important challenge with clinical implications. An innovative technique called radioluminescence microscopy has been developed to quantitatively and sensitively measure radionuclide uptake in single cells. The most important component of this technique is the scintillator, which converts the energy released during radioactive decay into luminescent signals. The sensitivity and spatial resolution of the imaging system depend critically on the characteristics of the scintillator, that is, the material used and its geometrical configuration. Scintillators fabricated using conventional methods are relatively thick and therefore do not provide optimal spatial resolution. A thin‐film Lu2 O3 :Eu scintillator is compared to a conventional 500 μm thick CdWO4 scintillator for radioluminescence imaging. Despite its thinness, the unique scintillation properties of the Lu2 O3 :Eu scintillator allow us to capture single‐positron decays with fourfold higher sensitivity, which is a significant achievement. The thin‐film Lu2 O3 :Eu scintillators also yield radioluminescence images where individual cells appear smaller and better resolved on average than with the CdWO4 scintillators. Coupled with the thin‐film scintillator technology, radioluminescence microscopy can yield valuable and clinically relevant data on the metabolism of single cells. Abstract : Thin‐film Lu2 O3 :Eu scintillators are used to successfully produce high‐resolution images of glucose uptake in human cancer cells. The sensitivity of this novel material is quantified and shown to be a fourfold improvement over previously used thicker CdWO4 ‐based scintillators. This work has key implications for high‐resolution and real‐time imaging of cell metabolism using radiotracers.